Puerperas' perception concerning the care provided by the health team in pospartum - Juliana Fechine Braz de Oliveira; Glauberto da Silva Quirino; Dafne Paiva Rodrigues (Universidade Federal do Ceará, 2012)
The aim of this research was to investigate how puerperas experience the transition to maternal role based on care offered by the health team in the hospital and home context and to identify the knowledge acquired by puerperas concerning the care in postpartum. This is an exploratory and descriptive study with qualitative approach, with puerperas that performed prenatal tests in Family Health Strategy units, from June to August 2007. They used interviews, performed in home-visits. The categories analyzed were: women's feelings experienced in postpartum; women's knowledge on the inherent care to postpartum; extension of care to puerperas at home; and puerperas' satisfaction with the care received. The main kinds of care mentioned were: breastfeeding; feeding; family planning; and care to the newborn. It was noticed that the postpartum is assisted regularly, and the care was mostly addressed to newborns, with insufficient attention to puerperas.